2011
DOI: 10.1007/s10532-011-9455-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tertiary butyl alcohol (TBA)-utilizing organisms in BioGAC reactors using 13C-DNA stable isotope probing

Abstract: Biodegradation of the gasoline oxygenates methyl tertiary-butyl ether (MTBE) and ethyl tertiary-butyl ether (ETBE) can cause tertiary butyl alcohol (TBA) to accumulate in gasoline-impacted environments. One remediation option for TBA-contaminated groundwater involves oxygenated granulated activated carbon (GAC) reactors that have been self-inoculated by indigenous TBA-degrading microorganisms in ground water extracted from contaminated aquifers. Identification of these organisms is important for understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…With PCR products from the enrichment cultures, about 95 and 60% of the complete mdpJ and mdpK genes, respectively, were sequenced, showing Ͼ99% identity to the mdpJK genes from strain L108. This high degree of sequence identity is not surprising, as it has already been found that not only mdpJ but also other genes related to MTBE degradation are obviously well conserved among MTBE-and TBA-metabolizing bacteria (3,39,45).…”
Section: Detection Of Alkenes In Cultures Grown On Fuel Oxygenatesmentioning
confidence: 60%
“…With PCR products from the enrichment cultures, about 95 and 60% of the complete mdpJ and mdpK genes, respectively, were sequenced, showing Ͼ99% identity to the mdpJK genes from strain L108. This high degree of sequence identity is not surprising, as it has already been found that not only mdpJ but also other genes related to MTBE degradation are obviously well conserved among MTBE-and TBA-metabolizing bacteria (3,39,45).…”
Section: Detection Of Alkenes In Cultures Grown On Fuel Oxygenatesmentioning
confidence: 60%
“…Thus far, all mdpJ genes and the corresponding proteins detected in pure cultures and enrichments associated with MTBE or TBA degradation were highly similar (3,38). The amino acid sequences of MdpJ found for strains PM1 and L108, for example, showed 97% identity.…”
Section: Discussionmentioning
confidence: 85%
“…In strain PM1, the oxygenase and reductase are encoded by the mdpJ and mdpK genes, respectively, which show about 97% identity to the corresponding sequences found in strain L108. Recently, the importance of MdpJ in TBA metabolism has also been demonstrated by 13 C metabolomic and proteomic stable isotope probing (SIP) approaches investigating oxygenate degradation in mixed cultures (3,4). It is likely that MdpJ is also involved in TAA degradation, as strains L108 and PM1 could metabolize TAME and TAA (31,38).…”
mentioning
confidence: 99%
“…Any TRFLP fragment illustrating an increase in relative abundance in the heavy fraction of the samples (exposed to labeled substrate) compared to the controls (exposed to unlabeled substrate) is identified (using 16S rRNA gene clone libraries) as the putative degrader. The method has been used to identify the microorganisms involved in the degradation of numerous contaminants (4,15,21,34,40,51,58,64,65). In the current study, a range of sources (contaminated site sediment, agricultural soils, and wastewater treatment samples) were examined for anaerobic MTBE degradation potential.…”
mentioning
confidence: 99%